Implementation of Accrual Based Accounting on Regional Property in Indonesia: Competence Employees and Organizational Commitments Perspective - Firmansyah, Amrie; Wibowo, Puji; Puspitarini, Intan (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to examine the effect of employee competence and organizational commitment on the implementation of accrual accounting on the regional property in Indonesia. There was a change in the accounting system from cash to accruals to full accruals in 2015 in Indonesia Government. It has a significant impact on the adoption of accounting for regional assets dominated by fixed assets. The testing method employed in this research is quantitative. This study used a questionnaire as a tool to collect data from the respondents. The population in this study is the manager of regency/city government goods in the Province of Bali/Yogyakarta Special Region. The sample that can be used in this study amounted to 241 respondents regarding the number of questionnaires that have been filled by respondents through Google form. The findings of this study suggest that employee competence is associated with the implementation of accrual- based accounting on regional property. In contrast, organizational commitment is not associated with the implementation of accrual-based accounting on regional property. The result of this study indicates that increasing the competence of regional property management employees is essential to be conducted by local governments in Indonesia to support the improvement of the quality of financial statements. Also, the employees have no choice when working as civil servants in the area so that employees feel that in whatever institution they are placed in, they assume that the agency is the best in their work.